2013
DOI: 10.1016/j.ydbio.2012.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Mycn is essential for mouse ventricular wall morphogenesis

Abstract: MYCN is a highly conserved transcription factor with multifaceted roles in development and disease. Mutations in MYCN are associated with Feingold syndrome, a developmental disorder characterized in part by congenital heart defects. Mouse models have helped elucidate MYCN functions; however its cardiac-specific roles during development remain unclear. We employed a Cre/loxp strategy to uncover the specific activities of MYCN in the developing mouse myocardium. Myocardial deletion of Mycn resulted in a thin-myo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 107 publications
(197 reference statements)
3
32
1
Order By: Relevance
“…We established crosses to obtain embryos simultaneously deleted for a conditional Mycn allele (cKO-Mycn) and activated for iMOS T1Myc with the Nkx2.5-Cre driver ( Fig 3B). Embryos in which Mycn has been deleted but the iMOS mosaic is not activated are not viable past E10.5-E11.5 (Fig 3B), in accordance with the phenotype previously reported for Mycn deletion in cardiomyocytes 15 . Similarly, iMOS T1Myc activation on a wild type or Mycn-heterozygous background (iMOS-Myc) does not produce any phenotypic alteration 12 .…”
Section: Forced Myc Expression In a Mosaic Fashion Is Sufficient To Rsupporting
confidence: 91%
See 2 more Smart Citations
“…We established crosses to obtain embryos simultaneously deleted for a conditional Mycn allele (cKO-Mycn) and activated for iMOS T1Myc with the Nkx2.5-Cre driver ( Fig 3B). Embryos in which Mycn has been deleted but the iMOS mosaic is not activated are not viable past E10.5-E11.5 (Fig 3B), in accordance with the phenotype previously reported for Mycn deletion in cardiomyocytes 15 . Similarly, iMOS T1Myc activation on a wild type or Mycn-heterozygous background (iMOS-Myc) does not produce any phenotypic alteration 12 .…”
Section: Forced Myc Expression In a Mosaic Fashion Is Sufficient To Rsupporting
confidence: 91%
“…An alternative view would be that Mycn-deficient cells are not actively eliminated but just diluted out due to their limited ability to proliferate. To discriminate between these possibilities, given that Mycn-deficient cardiomyocytes do not autonomously display an increased apoptotic rate 15 and that apoptosis is a hallmark of Myc-induced cell competition in the developing mouse heart, we performed TUNEL analysis.…”
Section: Cell Competition Contributes To the Rescue Of Mycn-deficientmentioning
confidence: 99%
See 1 more Smart Citation
“…Tissue-specific inactivation studies revealed organ-specific functions of both c-myc and N-myc . Roles of N-myc were demonstrated in brain (Knoepfler et al, 2002), lung (Okubo et al, 2005), retina (Martins et al, 2008), hematopoietic stem cells (Laurenti et al, 2008), ear (Dominguez-Frutos et al, 2011), heart (Harmelink et al, 2013), and olfactory development (Wittmann et al, 2014). Even though, these studies did not analyze how N-myc regulates global gene expression during morphogenesis, few of these demonstrated functional compensation or redundancy between Myc family members.…”
Section: Introductionmentioning
confidence: 99%
“…And mice engineered to express 15% MYCN showed severe cardiac muscle hypoplasia and lethality between E12.5 and E14.5 (Moens et al 1993). The essential roles of MYCN in lung and heart development (Okubo et al 2005;Harmelink and Jiao 2010;Harmelink et al 2013), as well as in the development of the central nervous system (CNS) (Knoepfler et al 2002), limbs (Ota et al 2007), kidneys (Nakhai et al 2008), and inner ear (Domínguez-Frutos et al 2011) were confirmed and/or further defined by conditional MYCN deletion at these sites (see below for further discussion).…”
Section: Dose-dependent Control Of Embryonic Development By Mycn and Mycmentioning
confidence: 91%